2020
DOI: 10.1073/pnas.2002110117
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of C9ORF72–SMCR8–WDR41 reveals the role as a GAP for Rab8a and Rab11a

Abstract: A massive intronic hexanucleotide repeat (GGGGCC) expansion in C9ORF72 is a genetic origin of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Recently, C9ORF72, together with SMCR8 and WDR41, has been shown to regulate autophagy and function as Rab GEF. However, the precise function of C9ORF72 remains unclear. Here, we report the cryogenic electron microscopy (cryo-EM) structure of the human C9ORF72–SMCR8–WDR41 complex at a resolution of 3.2 Å. The structure reveals the dimeric assembly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 50 publications
8
69
2
Order By: Relevance
“…The secondary structure predicted by WDSP, a database for WD40 proteins, also predicted a similar large loop extending from the WDR41 β-propeller (Ma et al, 2019; Y. Wang et al, 2015). Although not available at the start of our study, two recently reported cryo-EM structures for the WDR41-C9orf72-SMCR8 complex validate this prediction for the overall structural organization of WDR41 and showed that the interaction with SMCR8-C9orf72 is via the WDR41 β-propeller (23,24).…”
Section: Prediction Of a Novel Mechanism For The Wdr41-pqlc2 Interactionsupporting
confidence: 75%
“…The secondary structure predicted by WDSP, a database for WD40 proteins, also predicted a similar large loop extending from the WDR41 β-propeller (Ma et al, 2019; Y. Wang et al, 2015). Although not available at the start of our study, two recently reported cryo-EM structures for the WDR41-C9orf72-SMCR8 complex validate this prediction for the overall structural organization of WDR41 and showed that the interaction with SMCR8-C9orf72 is via the WDR41 β-propeller (23,24).…”
Section: Prediction Of a Novel Mechanism For The Wdr41-pqlc2 Interactionsupporting
confidence: 75%
“…Farg et al [ 43 ] first reported C9orf72 to interact with RAB1, RAB5, RAB7 and RAB11. Webster et al [ 22 ] confirmed that C9orf72 associates with GTP-bound RAB1A and the ULK1 complex, and it has been demonstrated that C9orf72 in complex with SMCR8 and WDR41 is a GEF for RAB8A, RAB11A, and RAB39B, and that its loss perturbs autophagy in neurons [ 27 , 29 , 31 , 89 ]. We detected only RAB1B in our SMCR8 and C9orf72 interactomes (Tables S1 , S2 ), but failed to confirm binding of V5-tagged RAB1A, a paralog highly similar in sequence to RAB1A, with SMCR8 in direct co-IP experiments.…”
Section: Resultsmentioning
confidence: 99%
“…mTORC1 negatively regulates autophagy, so the ARF1-mTORC1 connection could explain how haploinsufficient C9orf72 leads to a decrease in autophagy, which has in turn been linked to multiple neurodegenerative diseases 30 . While our paper was under review, a cryo-EM structure of a dimeric form of this complex was reported and proposed to serve as a GAP for RAB8A and RAB11A 31 . The relative roles of GAP activity with respect to different small GTPases in normal function and disease remain to be determined.…”
mentioning
confidence: 99%